Analisis Keseimbangan Bandwidth Menggunakan Dua ISP dengan Metode Per Connection Classifier (PCC) Load Balancing Berbasis Mikrotik (Studi Kasus pada Badan Pengelolaan Pajak Daerah Kota Palembang) - Cendri Ariyanto (Jurnal Jaringan Komputer dan Keamanan, 2021)
The need for internet access continues to increase along with the development of information technology, particularly in supporting data exchange activities in government agencies. The Palembang City Regional Tax Management Agency utilizes two internet service providers (ISPs) to support operational activities, but their bandwidth distribution has not yet been optimized. This study aims to analyze bandwidth balancing using two ISPs with the Mikrotik-based Per Connection Classifier (PCC) load-balancing method. The research method used was action research, consisting of the stages of diagnosis, action planning, action implementation, evaluation, and learning. The test results showed that the implementation of the PCC method significantly increased internet access speed. Before load balancing, video access speed on the GASNET ISP was 14.6 Mbps and on the SISNET ISP was 7.5 Mbps. After PCC implementation, access speeds increased to 95.7 Mbps on GASNET and 56.3 Mbps on SISNET. Additionally, speed test results showed an increase in download speed from 37.29 Mbps to 104.15 Mbps and in upload speed from 46.01 Mbps to 144.29 Mbps. Thus, the PCC method proved effective in optimizing bandwidth utilization and balancing traffic loads across two internet connections.